A Bayesian approach for the zero-inflated cure model: an application in a Brazilian invasive cervical cancer database. Issue 12 (10th September 2022) - de Souza, Hayala Cristina Cavenague; Louzada, Francisco; Ramos, Pedro Luiz; de Oliveira Júnior, Mauro Ribeiro; Perdoná, Gleici da Silva Castro
ABSTRACT: This paper aims to discuss the Bayesian estimation approach for the zero-inflated cure class of models, which extends the standard cure model by accommodating zero-inflated data in the survival analysis context. A comprehensive simulation study is carried out to assess the performance of the estimation procedure. A new estimation methodology is illustrated using a real dataset related to women diagnosed with invasive cervical cancer in Brazil.